2017
DOI: 10.1038/s41598-017-16485-0
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy protects pancreatic beta cell mass and function in the setting of a high-fat and high-glucose diet

Abstract: Autophagy is a major regulator of pancreatic beta cell homeostasis. Altered autophagic activity has been implicated in the beta cells of patients with type 2 diabetes, and in the beta cells of obese diabetic rodents. Here, we show that autophagy was induced in beta cells by either a high-fat diet or a combined high-fat and high-glucose diet, but not by high-glucose alone. However, a high-glucose intake alone did increase beta cell mass and insulin secretion moderately. Depletion of Atg7, a necessary component … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
2
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 30 publications
(48 reference statements)
6
34
2
2
Order By: Relevance
“…IAPP is co‐produced and co‐secreted with insulin by pancreatic β‐cells. The biosynthesis of insulin by β‐cells, like that of IAPP, is a multistep process, and mutations in the pre‐proinsulin gene, or disruptions in posttranslational modifications at any major stage, can result in the formation of proteotoxic aggregates and activation of cellular stress mechanisms leading to β‐cell toxicity and diabetes . Insulin is initially translated in the cytosol as a pre‐prohormone (pre‐proinsulin), which is translocated across the ER membrane where it is enzymatically cleaved to form proinsulin .…”
Section: Insulin Misfolding and Other Signals Of Proteotoxicity In DImentioning
confidence: 99%
See 3 more Smart Citations
“…IAPP is co‐produced and co‐secreted with insulin by pancreatic β‐cells. The biosynthesis of insulin by β‐cells, like that of IAPP, is a multistep process, and mutations in the pre‐proinsulin gene, or disruptions in posttranslational modifications at any major stage, can result in the formation of proteotoxic aggregates and activation of cellular stress mechanisms leading to β‐cell toxicity and diabetes . Insulin is initially translated in the cytosol as a pre‐prohormone (pre‐proinsulin), which is translocated across the ER membrane where it is enzymatically cleaved to form proinsulin .…”
Section: Insulin Misfolding and Other Signals Of Proteotoxicity In DImentioning
confidence: 99%
“…Elevated levels of PI have been shown to be correlated to the degree of β‐cell secretory impairment in T2D patients . In the β‐cell, transport‐competent secretory peptide precursors, including PI, are regulated by autophagy, whereas efficient clearance of transport‐incompetent mutated forms of PI by alternative degradative pathways may be necessary to avoid β‐cell proteotoxicity . Insulin resistant Akita and db/db mice, as well as Zucker diabetic fatty rats display increased autophagosome flux, and disrupting autophagy in these models drives β‐cell UPR stress and the progression of diabetes .…”
Section: Insulin Misfolding and Other Signals Of Proteotoxicity In DImentioning
confidence: 99%
See 2 more Smart Citations
“…Although autophagy is typically recognized as a pro-survival mechanism, the consequences of excessive autophagy can lead to cell dysfunction and autophagic cell death, known as type II programmed cell death. Previous studies on the role of autophagy in the pathophysiology of diabetes examined the autophagic process in β cells [29]. Additionally, studies have shown that autophagy plays an important role in neurodegenerative disease [30].…”
Section: Introductionmentioning
confidence: 99%